Pengaruh Corporate Environmental Disclosure dan Corporate Governance Terhadap Risiko Bank Pada Perbankan Umum di Indonesia - Umniyah Aszahro; Rida Rahim (Fakultas Ekonomi Universitas Andalas, 2022)
The research design used is a hypothesis testing design. The population in this study were all conventional commercial banks listed on the IDX in 2014-2019. The sampling method used is purposive sampling method. The sample of this research is 10 commercial banks. The data analysis method used is the panel data method. The results of this study indicate: Corporate Environmental Disclosure has a negative and insignificant effect, Corporate Governance represented by institutional ownership and managerial ownership has a negative and insignificant effect, but the female board of directors has a positive and significant effect, while the independent board of commissioners has a positive and insignificant effect on bank risk. The standard deviation of ROA as a proxy for bank risk variables shows an R squared value of 34.36% while the remaining 65.64% is influenced by other parties not examined in this study. The results of this study must be considered because they are able to contribute to the literature that can affect bank risk.